Heart failure and the development of atrial fibrillation in Hispanics, African Americans and non-Hispanic Whites. (15th November 2018) - Shulman, Eric; Shah, Tina; Mazori, Alon Y.; Chudow, Jay J.; Kargoli, Faraj; Nevelev, Dmitriy; Romero, Jorge; Di Biase, Luigi; Fisher, John; Gross, Jay; Ferrick, Kevin J.; Krumerman, Andrew
Highlights: Heart failure (HF) is a common risk factor for atrial fibrillation (AF). African Americans and Hispanics have a higher HF burden, but lower prevalence of AF than Whites. 48, 315 individuals and a subcohort of 3851 with HF were followed for the development of AF. Hispanic and African Americans with and without HF had a lower risk to developed AF than Whites. Prevalence of heart failure by race is not an explanatory factor for the "racial paradox."